2019
DOI: 10.3991/ijet.v14i14.10310
|View full text |Cite
|
Sign up to set email alerts
|

Student Academic Performance Prediction using Supervised Learning Techniques

Abstract: Automatic Student performance prediction is a crucial job due to the large volume of data in educational databases. This job is being addressed by educational data mining (EDM). EDM develop methods for discovering data that is derived from educational environment. These methods are used for understanding student and their learning environment. The educational institutions are often curious that how many students will be pass/fail for necessary arrangements. In previous studies, it has been observed that many r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 7 publications
3
52
0
3
Order By: Relevance
“…Outcomes reveal better accuracy due to the reference of family expenditure, such as a natural gas, electricity, telephone, water, and accommodation, and students' personal data, such as gender, marital status, and employment, etc. To enhance engineering students' performance, a study by [1] identified the factors that can affect student success in this tough major. The study focused on the use of J48 and REP Tree algorithms to elicit the type of relationship between social parameters and student performance and predicting students' performance in their third semester.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Outcomes reveal better accuracy due to the reference of family expenditure, such as a natural gas, electricity, telephone, water, and accommodation, and students' personal data, such as gender, marital status, and employment, etc. To enhance engineering students' performance, a study by [1] identified the factors that can affect student success in this tough major. The study focused on the use of J48 and REP Tree algorithms to elicit the type of relationship between social parameters and student performance and predicting students' performance in their third semester.…”
Section: Related Workmentioning
confidence: 99%
“…The prediction of student academic performance helps in identifying weak students who will struggle with their studies. Science and IT majors are among the hardest at college level [1], [2]. Therefore, the management of computer and IT related institutions take essential steps to detect and correct the way for weak students.…”
Section: Introductionmentioning
confidence: 99%
“…As we have just seen, the studies seem to focus on the same algorithms: the SVM, the Naïve Bayes, the decision trees, as well as the logistic regression [1,[4][5][6]8]. The study of existing works has led, on many occasions, to note the points which make this task difficult [8]. These difficulties are intrinsically linked to the nature of the data to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Another point that can greatly reduce the performance of predictions is the fact that the datasets considered are generally poorly balanced. It is only very recently that some studies are interested in Random Forests (RF) to solve this problem [2,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Various supervised learning algorithms and neural networks from the first group are applicable for educational data: for example, J48, Non-Nested Generalisation (NNge) and Multilayer Perceptron (MLP) [15], Random Forest [16], ensemble [17], Deep Learning [18,19]. Clustering methods like k-means [20,21], document frequency method and support vector machines [22] for students' data also belong to this group.…”
mentioning
confidence: 99%